Strategi Pendistribusian Pupuk dalam Meningkatkan Perekonomian Petani Menurut Ekonomi Syariah pada Kelompok Tani Sido Rukun Desa Wonosari Kabupaten Musi Rawas - Mellia Dewi; Hoirul Amri; Rijalush Shalihin; Fadhilatul Hasanah (AL-MUNAWWIR: Jurnal Komunikasi, Pendidikan, & Syari'ah, 2026)
This study aims to identify the strategies of fertilizer distribution and the application of Islamic economic principles in improving the farmers’ economy in the Sido Rukun Farmers Group, Wonosari Village, Musi Rawas Regency. This research uses a qualitative method with a descriptive approach, and data were collected through interviews, observations, and documentation involving both administrators and group members. The results show that the fertilizer distribution strategy is not solely focused on economic profit but also emphasizes Islamic values such as honesty, fairness, trustworthiness, transparency, and mutual assistance. The management provides clear and transparent information regarding the availability, price, and quality of fertilizers and prioritizes deliberation in the distribution process, especially when supplies are limited. Supporting factors include strong cooperation between administrators and members, open communication, and government support through subsidized fertilizers. However, several challenges are encountered, including limited fertilizer stock, delays in distribution, limited capital, unpredictable weather conditions, and inadequate storage facilities. Overall, the implemented strategy is considered effective in helping farmers meet their fertilizer needs and improve their welfare.